Using nitro-oxidized cellulose nanofibrils from banana rachis to engineer fracture toughness in cementitious concrete matrix - Ngesa Ezekiel Mushi; Regan Mahoo; Edward Rwegasila (Discover Chemical Engineering)
Abstract Concrete is a robust material under compressive load but lacks toughness, making it prone to brittle failure. In a recent study, researchers engineered concrete at the nano level using nitro-oxidized cellulose nanofibrils (NOCNF) to improve its plasticity. After curing for twenty-eight days, they found that adding a small amount of NOCNF significantly improved the concrete’s toughness. Specifically, the impact fracture energy increased by 70% with 0.1 wt% NOCNF, the flexural toughness increased by 93.3% with 0.5 wt% NOCNF, and the compressive toughness increased by 23.30% at the same concentration. Furthermore, adding 0.5% NOCNF led to a 79% decrease in thermal conductivity. Electron dispersive X-ray analysis revealed that the improved properties were due to the increased formation of calcium-silicate hydrates with NOCNF addition. The nanofibrils, with a diameter of 5 nm and a negative charge with a degree of oxidation of 0.455 mmol/g, probably interact well with cations from the clinker, enhancing the hydration process and filling micro- and nano-voids. This nanotechnology approach shows promise not only for strengthening concrete ductility but also for creating materials with multifunctional properties using an eco-friendly component found in nature.